2022
DOI: 10.15251/cl.2022.192.117
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of some optical and physical properties of As11.2S48.0Sb28.8Te12.0 and As20.8S48.0Sb19.2Te12.0 nanostructured polycrystalline semiconductors

Abstract: This work presents the characterization of As-S-Sb-Te nanostructured polycrystalline semiconductors by X-ray fluorescence (XRF), X-ray diffraction (XRD), electron microscopy (SEM), optical as well as photoelectric methods. The XRD patterns have been shown the presence of amorphous and nanocrystalline phases with the main structural units As2S3, Sb2S3 and Sb2Те3. The IR transmission spectra show a high transparence just with a single weak absorption band about ν=2340 cm-1 caused of the presence of H2S impurity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This paper presents the extension of our previous experimental studies [5,6] regarding new chalcogenide materials in quaternal As-S-Sb-Te system. As shown in our early paper [5] chalcogenide materials, which have the composition similar to this one, namely As 11.2 S 48.0 Sb 28.8 Te 12.0 and As 20.8 S 48.0 Sb 19.2 Te 12.0 demonstrate polycrystalline structure.…”
Section: Introductionmentioning
confidence: 66%
“…This paper presents the extension of our previous experimental studies [5,6] regarding new chalcogenide materials in quaternal As-S-Sb-Te system. As shown in our early paper [5] chalcogenide materials, which have the composition similar to this one, namely As 11.2 S 48.0 Sb 28.8 Te 12.0 and As 20.8 S 48.0 Sb 19.2 Te 12.0 demonstrate polycrystalline structure.…”
Section: Introductionmentioning
confidence: 66%
“…Some experimental results on XRD, EDS and micro-Raman spectroscopy of As-S-Sb-Te system as bulk, powder and thin film samples were reported in [7,8]. It has been shown that the quaternary compounds As 1.17 S 2.7 Sb 0.83 Te 0.40 , As 1.04 S 2.4 Sb 0.96 Te 0.60 and As 0.56 S 2.4 Sb 1.44 Te 0.60 have a polycrystalline structure, and the other one As 0.63 S 2.7 Sb 1.37 Te 0.30 has a amorphous structure with broad peaks specific for non-crystalline materials.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the quaternary compounds As 1.17 S 2.7 Sb 0.83 Te 0.40 , As 1.04 S 2.4 Sb 0.96 Te 0.60 and As 0.56 S 2.4 Sb 1.44 Te 0.60 have a polycrystalline structure, and the other one As 0.63 S 2.7 Sb 1.37 Te 0.30 has a amorphous structure with broad peaks specific for non-crystalline materials. Studying of photoelectric properties allows obtaining information about the generation and recombination processes in chalcogenide semiconductors [7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters for Sb 2 S 3 -As 2 S 3 -Sb 2 Te 3 compositions were calculated from their chemical formula obtained by EDS experiments [8]. Some optical and physical properties of As 11.2 S 48.0 Sb 28.8 Te 12.0 and As 20.8 S 48.0 Sb 19.2 Te 12.0 nano-structured polycrystalline semiconductors were reported in [9,10].…”
Section: Introductionmentioning
confidence: 99%